Pengaruh Corporate Governance Terhadap Manajemen Laba: (Studi Kasus Pada Perusahaan Sektor Industri Konsumsi Yang Terdaftar Di BEI Tahun 2020-2022) - Aramita Nur Aflikhah; Sri Laksmi Pardanawati; LMS Kristiyanti (Jurnal Ilmiah Keuangan Akuntansi Bisnis (JIKAB), 2023)
The aims of this research is to examine the influence of corporate governance mechanism to earning management. This type of research is a descriptive quantitative aims. Corporate governance mechanisms used include instructional ownership, audit committees, and independent board of commissioners. The study samples were 36 consumer goods industry manufacturing companies listed on the Indonesia Stock Exchange, selected using purposive sampling techniques during the 2020-2022 research period. Data were collected using secondary data from consumer goods industry manufacturing companies listed on the Indonesia Stock Exchange. Data analysis methods use multiple regression analysis. The results of the analysis showed that (1) instructional ownership had a significant positive effect on profit management, (2) audit committees had a significant negative effect on profit management, (3) independent board of commissioners had no significant effect on profit management.